Objective Disease Monitoring Strategies from a Tertiary Inflammatory Bowel Disease Center in Hungary - Lontai, Livia; Kürti, Zsuzsanna; Gonczi, Lorant; Komlódi, Nóra; Balogh, Fruzsina; Iliás, Ákos; Lakatos, Peter L. (Turkish Journal of Gastroenterology, 2023)
Background: Emerging data suggest that a treat-to-target approach and early therapeutic intervention using regular objective disease assessment leads to improved outcomes. Our aim was to evaluate the value of objective disease monitoring during regular follow-up in a single tertiary inflammatory bowel disease center. Methods: Consecutive inflammatory bowel disease patients (n = 161, Crohn’s disease: 118/ulcerative colitis: 43; biological therapy: 70%) were included and followed up for 1 year between January and December 2018. Data on clinical disease activity, biomarkers, endoscopy, imaging, outpatient visits, treatment optimization, hospitalization, and surgery were collected. We compared the monitoring strategy according to the clinical activity (remission/flare/post-flare/continuous activity) every 3 months (assessment period). Results: In total, n = 644 assessment periods were evaluated. Biomarkers were evaluated in 82.9%-83.9% of patients in each assessment period regardless of clinical activity. Colonoscopy was more frequently performed in active disease (flare/continuous disease activity: 21.1%/18.9% vs. clinical remission: 10.1% per assessment period). Magnetic resonance imaging was performed in 7.7%-16.7%/ period in Crohn’s disease patients, while the use of computed tomography was low (2.4%/period) and mainly performed in active disease. Treatment optimization was more frequent in patients with active disease (biological start/dose optimization: 31.1%/33.8%/ period, steroid start: 13.2%/period). Patients with continuous activity (2.62), flare (2.45), and post-flare (2.05) had higher mean patient visit counts compared to remission (1.68/period). Conclusions: Objective monitoring strategy was applied with routine assessment of clinical activity and biomarkers. Fast-track colonoscopic evaluations were adapted to the clinical stage of the disease while screening colonoscopies and magnetic resonance imaging were frequently used. Objective monitoring resulted in the early optimization of medical therapy and frequent specialist follow-up visits. Cite this article as: Lontai L, Kürti Z, Gonczi L, et al. Objective disease monitoring strategies from a tertiary inflammatory bowel disease center in Hungary. Turk J Gastroenterol. 2023;34(5):508-515.